Firm Specific Fundamental Variables and Common Stock Returns - Poudel, Shiva Raj (Far Western Review, 2024)
The main objective of the study is to examine the impact of firm specific fundamental variables on cross-section of expected stock returns from the Nepali capital market. The data were collected form the sample of 48 firms actively traded in the Nepal stock exchange (NEPSE) for 12 years from mid-July 2011 to mid-July 2022 with 576 observations. The explained variable is common stock returns and the explanatory variables are firm specific fundamental variables such as market capitalization as proxied by firm size, book to market equity, earning yield and cash flow yield. The study examined that firm size, book to market equity, and earning yield (for only CGY and TY) have the significant negative impact on common stock returns in Nepali capital market. In contrast earning yield has the significant positive impact on dividend yield only. The cash flow yield has no significant impact on common stock returns in Nepali capital market.